Pengaruh Nilai Tukar (Kurs), Inflasi dan Tingkat Suku Bunga Tabungan terhadap Volume Tabungan Masyarakat pada Bank Umum Pemerintah di Indonesia (Periode 2013-2017) - Ni Kadek Rita Yanti; A. A. Ketut Jayawarsa; I Gde Agung Wira Pertama (Warmadewa Economic Development Journal (WEDJ), 2020)
This study entitled The Effect of Exchange Rate (Exchange), Inflation, and Interest Rates on Savings Against the Volume of Public Savings in Government Commercial Banks in Indonesia for the period 2013-2017. The formulation of the problem: How the Effect of Exchange Rate (Exchange), Inflation, and Interest Rate Savings Against the Volume of Public Savings at Government Commercial Banks in Indonesia Period 2013-2017 simultaneously and partially. The purpose of this study are: To analyze the effect of Exchange Rate (Exchange ), Inflation, and Interest Rate Savings Against the Volume of Public Savings in Government Commercial Banks in Indonesia Period 2013-2017 simultaneously and partially. This research was conducted at the Government Commercial Bank through the website www.bi.go.id and www.ojk.go.id. The analytical tool used is Multiple Linear Regression Analysis, F Test (F-test), and t Test (t-test), before multiple linear regression analysis is carried out descriptive analysis of data and Classical Assumption Test, Results obtained from regression multiple linear is Y = 13,069 + 0,591 X1 + 0,040 X2 + 0,843 X3.